miR-30-5p-mediated ferroptosis of trophoblasts is implicated in the pathogenesis of preeclampsia - Zhang, Heng (Redox Biol, 2019)
Oxidative stress is a major cause of adverse outcomes in preeclampsia (PE). Ferroptosis, i.e. programmed cell death from iron-dependent lipid peroxidation, likely mediates PE pathogenesis. We evaluated specific markers for ferroptosis in normal and PE placental tissues, using in vitro (trophoblasts) and in vivo (rat) models. Increase in malondialdehyde content and total Fe(2+) along with reduced the glutathione content and glutathione peroxidase activity was observed in PE placenta. While the trophoblasts experienced death under hypoxia, inhibitors of ferroptosis, apoptosis, autophagy, and necrosis increased the cell viability. Microarrays, bioinformatic analysis, and luciferase reporter assay revealed that upregulation of miR-30b-5p in PE models plays a pivotal role in ferroptosis, by downregulating Cys2/glutamate antiporter and PAX3 and decreasing ferroportin 1 (an iron exporter) expression, resulting in decreased GSH and increased labile Fe(2+). Inhibition of miR-30b-5p expression and supplementation with ferroptosis inhibitors attenuated the PE symptoms in rat models, making miR-30b-5p a potential therapeutic target for PE.